THE ROLE OF EXTRACURRICULAR ACTIVITIES IN ENVIRONMENTAL MANAGEMENT OF AN ISLAMIC-VALUE-BASED SCHOOL - Rohimah Rohimah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Extracurricular activities are school-based initiatives aimed at developing the abilities of students, not only in terms of skill enhancement but also in gaining insights and knowledge while helping to shape the character of participants in their respective fields. In managing the school environment with an Islamic value system, there are inevitably numerous shortcomings. These may include a tight schedule for extracurricular practices, insufficient facilities, and a lack of maintenance for extracurricular inventories. It's not only the extracurricular activities that need attention; the factors influencing school environmental management must also be upheld. This ensures the execution of attitudes, the observance of rules, and adherence to school regulations. Similarly, implementing Islamic values places the responsibility on students to engage in religious activities while at school. This practice serves to facilitate a smoother workflow during various school activities, both inside and outside the classroom. This research aims to explore the role of extracurricular activities in the school environment management that implements Islamic values at Perguruan Rakyat 2 High School in Pondok Kelapa, East Jakarta. The application of Islamic values, encompassing faith (akidah), worship (ibadah), and morality (akhlak), serves as a foundational aspect of Islamic character education. These values are not only integrated into the formal learning process but also extend to various other activities within the educational institution. The successful implementation of these Islamic values relies on the support of educators or school authorities who are enthusiastic about reinforcing Islamic character education. Their dedication plays a crucial role in instilling these values, ensuring that they become ingrained in the character of students at Perguruan Rakyat 2 High School in Jakarta. This integration is achieved through a combination of structured learning activities and other engagements within the educational institution. The method employed in this research is a qualitative approach, specifically using a descriptive type. The research findings indicate that the application of Islamic values, in the form of written words derived from the obtained data sources, utilizes the Case Studies method. The aim is to obtain a comprehensive and in-depth overview. The results of this study reveal the roles of Islamic Education teachers and other educators in extracurricular activities within the school's environmental management that implements Islamic values at Perguruan Rakyat 2 High School in Jakarta. The development of extracurricular activities and the environmental management of the school, incorporating Islamic values, are found to be progressing well. This is attributed to the active involvement and optimal performance of Islamic Education teachers and other educators. The Case Studies method proves effective in providing a complete and nuanced understanding of the overall scenario.